Assessing clarity and erasability of commercially available pens for surgical site marking: a comparative study in human volunteers. Issue 1 (December 2016) - Sim, F.; Angadi, D.; Jarvis, G.; Porteous, M.
Abstract Background Marking the surgical site is a well-established part of pre-operative protocol and errors in marking have been implicated in wrong site surgery incidents and are a significant patient safety issue. There are many commercially available marker pens and anecdotally very little consistency in which pen is used or the clarity of marking. Previous studies have shown subjective differences between different pens and the current paper sought to support this evidence with objective data and widen the investigation of commercially available pens. Methods Eight marker pens were used to mark two separate sites on three caucasian volunteers. These marks were photographed and assessed by six observers before and after the application of chlorhexidine skin preparation. The observers were blinded to which pen was used for each mark, and rated the clarity of the marks subjectively. The photographs were assessed using image analysis software to give an objective measure of clarity against the skin. Results There was a wide variation between the clarity of marks made by the different pens, and also a wide variation in the resistance to skin preparation. The Pentel N50 pen was the outstanding best performing pen across all categories. Conclusions It is recommended that the Pentel N50 black marker pen be used for surgical site marking to improve patient safety and avoid adverse events.